Study on the influence of machine tool spindle radial error motion resulted from bearing outer ring tilting assembly. (May 2019) - Li, Xiaohu; Yan, Ke; Lv, Yifa; Yan, Bei; Dong, Lei; Hong, Jun
To reveal the spindle radial error motion characteristics in condition of bearing outer ring tilting assembly, mathematical method on spindle radial error motion were analyzed. Then, in real operation condition the natural frequency of the test rig was investigated. Experimental system and methods were designed to test axial thermal displacement, radial error motion and modal characteristic of spindle in condition of bearing outer ring tilting assembly. Results show that axial thermal extension and radial vertical rising of spindle front-end occurs during thermal displacement test. With the same outer spacer nonparallelism, the synchronous error motion and total error motion generally increase with spindle rotation speed, and reach a peak at certain rotation speed.